Impacto das experiências laboratoriais na aprendizagem dos alunos no ensino de química - Camuendo, Ana Paula Luciano Alichi (2006)
The present work is aimed at analysing the impact of chemistry teaching experiences with locally available alternative material. The purpose is to contribute to the improvement of teaching quality through the implementation of feasible experiences guidelines, under the conditions of Mozambique schools. The present research had as a departure point, the problem of the absence of laboratory experiences in the teaching of chemistry, noticed during the observation of UP students in the teaching pratice activities in the schools. To this fact I added the lack of interest, on the part of students, in learning Chemistry, the passivity and little motivation in learning this subject. I have supported the theoretical part of this research with readings from FREIRE (1996), PIAGET (1996), BECKER (2002), VYGOTSKY (1998), COLL (2001), and others. From them, I have found the epistemological foundations of education in the process of construction of knowledge, within the scope of the constructivist theory. The methodological approach is based on qualitative research and, in this context, I have developed a case study. Two schools have been selected, one im Maputo city and the other in Maputo Province, Boane District. The target group of this research were grade 8 students and teachers in the two above-mentioned secondary schools. The results of the research show that the experiences have a positive impact in the teaching-learning process, because besides upgrading the students level of learning, they raise a major interest, leading students to reflection, what allows the formation of curious, creative and active personalities